VERIFICAÇÃO DA SATISFAÇÃO DOS USUÁRIOS EM RELAÇÃO ÀS CARACTERÍSTICAS DE DUAS EDIFICAÇÕES EM MACEIÓ/AL - Bastos, Carlos; Weber, Ismal (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
In the housing context, post-occupation evaluation (APO) appears as an effective tool for systematic evaluation of the built environment, with the inclusion of the user in this process (MEIRA; OLIVEIRA, 1998). It is conceptualized by Roméro and Ornstein (2003) as a methodology that seeks to diagnose positive and negative aspects, from technical, economic, functional, aesthetic and behavioral factors of the environment in use, without losing sight of the opinions of designers, technicians, clients and users. This work has as main objective to verify the current situation of user satisfaction in relation to the medium-high standard multi-storey buildings of Maceió-AL. Through the collection of information provided by a local construction company and analysis of graphs made with the support of Excel computational tool. With the aid of the literature, the evaluation instrument used was diagnosed and proposed improvements.